The thioredoxin system and cancer therapy: a review - Mohammadi, Fariba; Soltani, Arash; Ghahremanloo, Atefeh; Javid, Hossein; Hashemy, Seyed Isaac (Cancer chemotherapy and pharmacology, 2019)
Thioredoxin (Trx), thioredoxin reductase (TrxR), and NADPH are key members of the Trx system that is involved in redox regulation and antioxidant defense. In recent years, several researchers have provided information about the roles of the Trx system in cancer development and progression. These reports indicated that many tumor cells express high levels of Trx and TrxR, which can be responsible for drug resistance in tumorigenesis. Inhibition of the Trx system may thus contribute to cancer therapy and improving chemotherapeutic agents. There are now a number of effective natural and synthetic inhibitors with chemotherapy applications possessing antitumor activity ranging from oxidative stress induction to apoptosis. In this article, we first described the features and functions of the Trx system and then reviewed briefly its correlations with cancer. Finally, we summarized the present knowledge about the Trx/TrxR inhibitors as anticancer drugs.